Estimation of location and scale parameters in two-parameter exponential distribution based on ranked set sample - Sukuman Sarikavanij (2018)
In this article, we are interested in simultaneous comparison of the location and scale estimators of a two-parameter exponential distribution based on simple random sample (SRS) and ranked set sample (RSS) by using generalized variance (GV). We suggest various RSS strategies to estimate the scale parameter. Their performances in terms of GV are compared with SRS strategy. Finally, we illustrate the minimum values of set size, n, based on RSS, which would result in smaller GV than that based on SRS. © 2014 Taylor and Francis Group, LLC.